The Effect of Modified Flipped Classroom Learning Assisted Students' Worksheets on English Reading Comprehension - Kiswati; Setyosari, Punaji; Kuswandi, Dedi; Suryati, Nunung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The flipped classroom is a possible learning model solution​ that can be used occasionally. With modification through various media tailored to students' needs, the modified flipped classroom has been proven to improve motivation and results. Studying in English lessons is at the upper middle level. This research aims to identify the influence of learning that a modified flipped classroom helps student worksheets toward English reading comprehension. This research applies quasi-research with a pre-test and post-test control group design. The participants in this research were 89 students. The experimental group (N=44) was taught to use a modified flipped Classroom, and the temporary control group (N=45) was taught to use a flipped Classroom. The researcher used statistical tests factorial anova and found a different understanding of significant reading​ between the two groups, Where the group that used the modified flipped classroom obtained better results. Research findings: the author tried to conclude that there is a difference in English reading comprehension between​ group students who received treatment by applying the modified flipped classroom model and those who obtained treatment using the flipped classroom model.